4, 5-Dichloro-2-octyl-4-isothiazolin-3-one (DCOIT) modifies synaptic transmission in hippocampal CA3 neurons of rats. (October 2017) - Wakita, Masahito; Shoudai, Kiyomitsu; Oyama, Yasuo; Akaike, Norio
Abstract: 4, 5-Dichloro-2-octyl-4-isothiazolin-3-one (DCOIT) is an alternative to organotin antifoulants, such as tributyltin and triphenyltin. Since DCOIT is found in harbors, bays, and coastal areas worldwide, this chemical compound may have some impacts on ecosystems. To determine whether DCOIT possesses neurotoxic activity by modifying synaptic transmission, we examined the effects of DCOIT on synaptic transmission in a 'synaptic bouton' preparation of rat brain. DCOIT at concentrations of 0.03–1 μM increased the amplitudes of evoked synaptic currents mediated by GABA and glutamate, while it reduced the amplitudes of these currents at 3–10 μM. However, the currents elicited by exogenous applications of GABA and glutamate were not affected by DCOIT. DCOIT at 1–10 μM increased the frequency of spontaneous synaptic currents mediated by GABA. It also increased the frequency of glutamate-mediated spontaneous currents at0.3–10 μM. The frequencies of miniature synaptic currents mediated by GABA and glutamate, observed in the presence of tetrodotoxin under external Ca 2+ -free conditions, were increased by 10 μM DCOIT. With the repetitive applications of DCOIT, the frequency of miniature synaptic currents mediated by glutamate was not increased by the second and third applications of DCOIT. Voltage-dependent Ca 2+ channels were not affected by DCOIT, but DCOIT slowed the inactivation of voltage-dependent Na + channels. These results suggest that DCOIT increases Ca 2+ release from intracellular Ca 2+ stores, resulting in the facilitation of both action potential-dependent and spontaneous neurotransmission, possibly leading to neurotoxicity. Highlights: 4, 5-Dichloro-2-octyl-4-isothiazolin-3-one (DCOIT) is an antifoulant. DCOIT increased the frequency of synaptic currents mediated by GABA and glutamate. The increase was mainly due to Ca 2+ release from intracellular Ca 2+ stores by DCOIT. DCOIT-induced excess facilitation of neurotransmission may result in neurotoxicity.